Hybrid Polyamide Microporous Membranes Obtained with Different Solvents - Airan Magalhães Moura; Joana Suelânia da Silva Lima; Natália Fernanda Santos Silva; Joanne Graziela Andrade Mendes; Carlos Antônio Pereira de Lima; Keila Machado de Medeiros (Materials Research)
This research explored a new approach that uses a waste material, polyamide 66 (PA66), as a raw material in the manufacture of membranes for the treatment of textile effluents. Membranes were produced by combining PA66 with silicon carbide (SiC) using the phase inversion technique, in the presence of magnesium chloride, using different solvents such as formic acid and hydrochloric acid. The SiC was characterized using X-ray diffraction and the grain size of the sample was measured. The membranes were characterized using various techniques, including water absorption, porosity, bubble point, average pore radius, contact angle, chemical resistance, water flow and effluent flow. The water-dye separation tests revealed a significant reduction in concentration. All the membranes showed a yield of over 99%, which demonstrates the potential of these membranes for this application.